2022
DOI: 10.3389/fsurg.2021.816501
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma Complicated by Echinococcal Cyst: A Case Report

Abstract: Hepatocellular carcinoma (HCC), combined with hepatic hydatid disease, is a rare clinical case, having certain specificity in clinical diagnosis and treatment. We report a case of HCC combined with hepatic hydatid disease treated in our clinic to arouse the attention of clinicians to the disease. A 54-year-old female patient was admitted to the clinic on October 31, 2016 because of “Intermittent upper abdominal pain and discomfort for 1 month.” Abdominal CT in the previous hospital showed liver space-occupying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Although both HCC and CE are common liver lesions with high incidence rates in the general population, their synchronous occurrence is very rare in clinical practice, especially in a non-cirrhotic liver [ 6 , 7 , 8 , 9 ]. Thus, in a recent study among 3300 patients with CE, the concomitant presence of HCC was found in only 13 cases (0.39%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both HCC and CE are common liver lesions with high incidence rates in the general population, their synchronous occurrence is very rare in clinical practice, especially in a non-cirrhotic liver [ 6 , 7 , 8 , 9 ]. Thus, in a recent study among 3300 patients with CE, the concomitant presence of HCC was found in only 13 cases (0.39%) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the popularization of tourism and migration of the population, CE is no longer just an endemic disease, but it has become a global health problem worldwide [ 4 ]. Even though both HCC and liver echinococcosis are common diseases, their coexistence, especially in the form of a coalescent lesion in a non-cirrhotic liver, is very rare in clinical practice [ 6 , 7 , 8 , 9 , 10 , 11 ]. The association between these two diseases is still not well-defined, with many contradictory reports in the previous literature [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic CE is widely distributed around the world in areas with developed agriculture and animal husbandry, and most commonly settles in the liver. [ 5 ] Various treatments like drug therapy, puncture, aspiration, injection, and reaspiration are applied to clinical practice, but the traditional surgical resection is still the main treatment. Although hepatic CE is relatively common in clinical practice, CE combined with liver cancer is rare in clinical practice, especially for some atypical cases, which is more difficult to diagnose.…”
Section: Discussionmentioning
confidence: 99%
“…Hydatid can involve any organ. The liver and lungs are the most frequently affected sites [4,5]. Hepatic hydatid is a life-threatening disease, mainly differentiated into cystic and alveolar forms, associated with infections of E. granulosus and E. multilocularis, respectively.…”
Section: Introductionmentioning
confidence: 99%